Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan Komplikasi pada Pasien Hipertensi di Puskesmas Bahu Kota Manado - Oktavia, Suryani; Natalia, Adriani; Fernandez, Gratsia (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Abstract Background. The number 1 killer in hypertension is complications of strokes and heart attacks, so there is a need for knowledge and prevention of these complications. Aim. To find out the relations between the level of knowledge and the complications of hypertensive prevention patients at Bahu Health Center in Manado City. Method. Using a Cross Sectional Analytic Approach with 79 total samples using non-probability sampling technique. Inclusion criteria in this study were hypertension sufferers aged ≥ 20 years and hypertension sufferers who visited the Bahu City Health Center in Manado City using the research instruments by hypertension Knowledge Level Scale questionnaire and a behavior questionnaire for preventing hypertension complications. The test is using the Chi Square test. This research was recommended by the Manado City National Unity and Politics Agency with number 200.1.2/BKBP/Rek-P/45/II/2023 and granted permission by the Manado City Health Office with number 39. D.02/KES/SDK-LIT /II/2023. Results. The results of the statistical test obtained a value of p = 0.018 (p <0.05) so it means that there is a relations between the level of knowledge and the complications of hypertensive prevention patients at the Bahu Health Center in Manado City. Discussion. There is a good level of knowledge of hypertensive patients which is obtained from health workers at the Bahu Health Center in Manado City, so there is a good impact with the behavior of preventing hypertension complications. Conclusion. The better the level of a person's knowledge about hypertension, the better their behavior to in order to prevent the complications, so it is advisable for the nurses to continue in providing the health education. Keywords: Behavior ; Hypertension ; Knowledge